Distribution Channels at PT. Mandala Raya Pilar Sakti Tupperware Sumedang - Solihin; Sutopo; Suharna (Journal of Bussines Management Basic, 2022)
The focus of this study aims to determine the distribution channel on the PT. Mandala Raya Pilar Sakti Tuperware Sumedang. The method used in this research is descriptive qualitative research method by conducting direct observation, conducting interviews, collecting data related to distribution channels on the PT. Mandala Raya Pilar Sakti Tuperware Sumedang. The sampling technique used is purpose sampling, namely the technique of sampling data sources with certain considerations. In this study five informants were used as informants. Whereas in analyzing data using the model of Miles and Huberman which states that there are three kinds of activities in qualitative data analysis, namely data reduction, data display, and conclusions drawing / verification. This research theory uses the theory of Tjiptono (2017: 347) with the following dimensions, 1) market considerations 2) product considerations 3) considerations about intermediaries and 4) company considerations. Based on the results of interviews, observations, and data analysis, it can be concluded that the marketing strategy at PD Vichi Pratama Aluminum Sumedang has carried out distribution channels well, but there are still some slight obstacles.